Communicating social support online: a new classification dichotomy for exploring coping in interaction concerning infertility. (19th October 2016) - Berry, Alison
Abstract: Objective: This study explores how social support is utilised in the context of an online infertility support group.Background: Social support is often studied to decipher how those with health concerns cope through communication and interaction.Method: Online socially supportive messages ( N = 200) were examined using a hybrid approach (i.e. deductive and inductive) to thematic analysis.Results: Analysis developed a dichotomy of social support (i.e. normative and transformative themes). This dichotomy creates a new theoretical framework for evaluating social support with implications for cognitive coping strategy. The normative and emotional themes were the most frequently represented in the studied context demonstrating overall network-level positivity. Messages did not demonstrate tangible support.Conclusion: Expected characteristics of emotional and informational support were demonstrated, but the forum included no tangible support. The support messages also possessed latent characteristics that should be further studied to understand implications for forum participant coping.